MAPPING THE TERRAIN OF TRANSFORMATIONAL LEADERSHIP, ORGANIZATIONAL COMMITMENT, AND EMPLOYEE ENGAGEMENT: A CONCEPTUAL FRAMEWORK - Sariono, Endro; Sugiono, Edi; Hasanudin, Hasanudin (Ridwan Institute, 2024)
Organizational commitment and transformational leadership play an important role in organizational success. This study explores the interrelationships between organizational commitment and employee engagement, highlighting their interconnected nature and implications for organizational effectiveness. A conceptual framework approach is used to map the interdependencies between transformational leaders, organizational commitment, and employees. Key findings and models from the selected studies are extracted to identify common themes and gaps. The conceptual framework aims to provide a foundational reference for future empirical studies and will assist practitioners in devising leadership strategies that effectively harness the potential of their workforce. The framework provides a comprehensive understanding of how leadership behaviors influence employees' emotional attachment to the organization and their subsequent engagement in their work roles.